Multimorbidity, polypharmacy, and mortality in older patients with pacemakers. Issue 1 (23rd November 2021) - Goto, Toshihiko; Mori, Kento; Nakayama, Takafumi; Yamamoto, Junki; Shintani, Yasuhiro; Wakami, Kazuaki; Fukuta, Hidekatsu; Seo, Yoshihiro; Ohte, Nobuyuki
Abstract: Background: The prevalence of multimorbidity and polypharmacy and its association with all‐cause mortality in older patients with pacemakers are largely unknown. We aimed to clarify the prevalence of multimorbidity and polypharmacy, and its association with all‐cause mortality in patients ≥75 years of age with pacemakers. Methods: We retrospectively investigated 256 patients aged ≥75 years (mean age 84.0 ± 5.3 years; 45.7% male) with newly implanted pacemakers. The study endpoint was all‐cause mortality ("with events"). Multimorbidity was defined as a Charlson Comorbidity Index ≥3. Polypharmacy was defined as the use of ≥5 medications. Results: During the follow‐up period (median, 3.1 years), 60 all‐cause deaths were reported. The Charlson Comorbidity Index (2.9 ± 1.9 vs. 1.7 ± 1.7, p  < .001) and prevalence of multimorbidity (56.7% vs. 26.0%, p  < .001) were significantly higher in deceased patients than in survivors. The number of drugs (6.9 ± 3.0 vs. 5.9 ± 3.3, p  = .03) and the prevalence of polypharmacy (78.3% vs. 63.8%, p  = .04) were significantly higher in patients with events than in those without events. The event‐free survival rate was significantly higher among patients without multimorbidity than in those with multimorbidity (log‐rank, p  < .001), and was also significantly higher among patients without polypharmacy than in those with polypharmacy (log‐rank, p  < .001). Multimorbidity (hazard ratio [HR]: 3.21; 95% confidence interval [CI]: 1.85–5.58; p  < .001) and polypharmacy (HR: 1.97; 95% CI: 1.03–3.77; p  = .04) were independent predictors of all‐cause mortality. Conclusions: Multimorbidity and its associated polypharmacy, which are common in the older population, are prevalent in patients with pacemakers and are independent predictors of poor prognosis. Abstract : Multimorbidity and its associated polypharmacy are prevalent in older patients with pacemakers. Polypharmacy is commonly observed regardless of disease prevalence. Multimorbidity, polypharmacy, and dependent ADL were independent predictors of poor prognosis in such patients.